Finance and Renewable Energy Development Nexus: Evidence from Sub-Saharan Africa - Chireshe, Jaison (International Journal of Energy Economics and Policy, 2020)
Renewable energy technologies provide an opportunity for sub-Saharan Africa countries to reduce energy poverty, achieve energy security and economic growth. This paper examined the relationship between financial development and renewable energy development using data from 17 selected sub-Saharan Africa countries for a 17-year period from 2000 to 2016. The study sought to understand whether financial development is associated with increased renewable energy generation capacity. The investigation adopted a fixed effects and system generalised methods of moments estimation approaches to understand the relationship between financial development and renewable energy development. The results show that financial development is positively correlated with renewable energy production capacity. These results imply that policy makers in sub-Sahara Africa must foster financial development in their respective countries to ensure increased investment in renewable energy production capacity. Keywords: Financial Development, Renewable Energy Development, Sub Saharan Africa JEL Classifications: G21, G42, O1 DOI: https://doi.org/10.32479/ijeep.10427